Peran Kader pada Program Bina Keluarga Balita (BKB) di Kampung KB Bangau Putih Kelurahan Parupuk Tabing Kota Padang - Ramadini, Suci; Sunarti, Vevi (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This background reseaarch is the participation of mothers has motivated to follow the BKB’s activity. The aim of the research is to see how the instructor influence on Bina Keluarga Balita(BKB) at Bangau Putih region Padang city. The influence of the instructor on BKB activity as a facilitator, motivator, and educator. This type of research is quantitative research which population is BKB members that are 50 persons and 33 of them become samples. The technique of collecting data is using questioner and the technique analysis is percentage. The research finding are 1) the research shows the instructor influence on BKB program at Bangau Putih region Padang city is well. 2) The research shows the instructor influence as a motivator on BKB program at Bangau Putih region Padang city categorize well. 3) The research shows the instructor influence as an educator on BKB program at Bangau Putih region Padang city categorize well. suggestion 1) the research suggests the instructors of BKB program at Bangau Putih region Padang city to keep their role as facilitator motivator and educator in the good program. 2) for DP3AP2KB to keep increasing program policies that will create the good program. 3) for the next researcher hopefully can be discussed this study deeper with different variable.